Self-cleaning cotton fabrics with good flame retardancy via one-pot approach. (October 2021) - Fu, Can; Ye, Wen; Zhai, Zhongjie; Zhang, Jing; Li, Pingyang; Xu, Baoyun; Li, Xiaolei; Gao, Fei; Zhai, Jinguo; Wang, De-Yi
Highlights: Non-halogenated method to functional cotton fabrics was developed. Functional fabrics displayed good flame retardancy via both gaseous and condensed phases. Functional fabrics exhibited excellent hydrophobic property. Abstract: The demand for multifunctional cotton fabrics possessing fire retardancy and hydrophobic self-cleaning property is soaring in recent years. In this work, non-halogen functional coatings by water-soluble phenylphosphinyl and amine-containing silanol (WPAS) were prepared through sol-gel method, in which functional cotton fabrics embraced with flame retardant (FR) and hydrophobic properties, simultaneously. The prepared WPAS coated functional fabrics reached as high as 30.4% for LOI value, and extinguished immediately after removing the ignitor in vertical fire test. Low-energy PO free radicals released by WPAS which was detected by TG-MS and TG-FTIR, captured high energy radicals such as H or OH radicals in the gas-phase. The char residue study from SEM, FTIR, Raman and XPS results found that P/Si/N thermostable ceramic char layer and aromatic carbonaceous structures formed which could provide a good barrier effect, effectively hindering diffusion of oxygen and transferring of heat into the flame zone. Additionally, water contact angle of functional cotton increased to 145° compared with cotton. As a result, it displayed hydrophobic self-cleaning property towards a series of common liquids in daily life. This convenient, eco-friendly one-pot approach is promising, and feasible for large-scale production of functional cotton fabrics with both excellent FR and hydrophobic self-cleaning properties to end-use industrial applications.